SIDE EFFECTS OF PROTON PUMP INHIBITORS DURING LONG TERM USE: FOCUS ON THE RESPIRATORY ORGANS - Дмитрий Иванович Трухан; Сергей Николаевич Филимонов (Медицина в Кузбассе)
Proton pump inhibitors (PPIs) are the most effective drugs for treating acid-related diseases. In recent decades, the use of PPIs has increased exponentially. For a long time, PPIs were considered completely safe drugs for both short-term and long-term use. However, modern clinical guidelines note that when prescribing PPIs in large doses for a long period, the possibility of side effects should be taken into account. In recent years, a number of foreign reviews have been published that examine the associations between PPIs and a number of diseases/conditions. We searched the PubMed and Scopus information databases for publications on the safety of PPI use, including sources up to 12.01.2023. In this review, we examined the effect of long-term use of PPIs on the respiratory system. Compared with other side effects, changes in the respiratory system have received less attention, but an increased risk of community-acquired pneumonia with long-term use of PPIs has been recognized as likely. Additional prospective studies are needed to elucidate the cause-and-effect mechanisms of the relationship between PPIs and brocho-obstructive diseases.